Energy balance aspect in KALI-30 GW high-voltage pulse power source. (12th September 2014) - Sharma, Archana; Mitra, S.; Vishnu Sharma, Senthil K.; Singh, Sandeep; Tewari, S.V.; Mittal, K.C.
Abstract: This paper elaborates the effect of unmatched stored energy in high-voltage high-energy pulsed power systems. High-voltage insulation failure of KALI system is analyzed thoroughly for its occurrence. According to the simulations and analysis energy mismatch of MARX generator and Blumlein transmission line is found to be the most significant cause for high-voltage failure of the system. MARX generator and Blumlein of KALI are redesigned to attain better energy balance at same voltage level. Observations, simulation and analytical results are illustrated in the following sections.